2013
DOI: 10.1074/jbc.m113.493155
|View full text |Cite
|
Sign up to set email alerts
|

Cloning and Structure-Function Analyses of Quinolone- and Acridone-producing Novel Type III Polyketide Synthases from Citrus microcarpa

Abstract: Background: Type III polyketide synthases (PKSs) synthesize various polyketide and alkaloid scaffolds. Results: QNS synthesizes quinolone as the single product, whereas ACS produces acridone as the major product. Conclusion: QNS and ACS are novel quinolone-and acridone-producing type III PKSs, respectively. Significance: Structure-function analyses of QNS and ACS provide insights into molecular bases for alkaloid biosyntheses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
49
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(51 citation statements)
references
References 46 publications
2
49
0
Order By: Relevance
“…The V98A substitution, hypothesized to be important for m-substituted phenyl substrate selectivity [24], was only found in R. graveolens ACS [58] but not in the other ACS and QNSs identified so far [59]. C. microcarpa ACS was found to be a highly promiscuous enzyme with a large active site cavity, being able to accept different starter CoAs to generate chalcone, benzophenone, and phloroglucinol scaffolds in addition to the production of 4-hydroxy-N-methylquinolone (29), 1,3-dihydroxy-N-methylacridone (30), and N-methyl-anthraniloyltriacetic acid lactone (31, Scheme 9).…”
Section: Acridone Synthase and Quinolone Synthasementioning
confidence: 80%
See 1 more Smart Citation
“…The V98A substitution, hypothesized to be important for m-substituted phenyl substrate selectivity [24], was only found in R. graveolens ACS [58] but not in the other ACS and QNSs identified so far [59]. C. microcarpa ACS was found to be a highly promiscuous enzyme with a large active site cavity, being able to accept different starter CoAs to generate chalcone, benzophenone, and phloroglucinol scaffolds in addition to the production of 4-hydroxy-N-methylquinolone (29), 1,3-dihydroxy-N-methylacridone (30), and N-methyl-anthraniloyltriacetic acid lactone (31, Scheme 9).…”
Section: Acridone Synthase and Quinolone Synthasementioning
confidence: 80%
“…Recently, the crystal structures of ACS (PDB ID: 3WD7) and QNS (PDB ID: 3WD8) from Citrus microcarpa were solved and wide active site entrances were found in both PKSs, which enabled the access of the bulky N-methylanthraniloyl-CoA [59]. The V98A substitution, hypothesized to be important for m-substituted phenyl substrate selectivity [24], was only found in R. graveolens ACS [58] but not in the other ACS and QNSs identified so far [59].…”
Section: Acridone Synthase and Quinolone Synthasementioning
confidence: 99%
“…Notably, triketide or tetraketide pyrone byproducts are not formed by the condensations of fatty acyl-CoA with two or three molecules of malonyl-CoA. Interestingly, the in vitro H 2 18 O incorporation experiment indicated that one of the two 18 O atoms is enzymatically incorporated into the product most likely by the nucleophilic cleavage of the thioester bond of the Cys-bound intermediate to generate the ␤-keto acid as the intermediate (whereas the other 18 O atom is exchangeable and spontaneously incorporated into the molecule). These results thus excluded the possibility of the ␤-ketoacyl-CoA intermediate but suggested that CsyB catalyzes the coupling of the ␤-keto acid intermediate and the enzyme-bound ␤-ketoacyl unit (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…As a result, the obtained product 3b afforded parent ion peaks [M ϩ H] ϩ at m/z 253 and m/z 255 in addition to m/z 251, indicating the incorporation of two 18 O atoms into the product (Fig. 8A).…”
mentioning
confidence: 99%
“…Type III PKSs are promiscuous enzymes that have a broad tolerance for diverse substrates and are able to catalyze multiple reactions [84,85]. Type III PKSs that use cyclic nitrogen-containing substrates have been previously characterized for their roles in alkaloid production [86][87][88]. However, unlike these previous studies the predicted substrate in TA metabolism, N-methyl-∆ 1 -pyrrolinium cation (19) [81].…”
Section: Tropane Alkaloid Biosynthesismentioning
confidence: 99%